Ответы и объяснения

Лучший Ответ!
2013-07-07T18:28:50+04:00

\frac{x^2}{3}+\frac{48}{x^2}=10(\frac{x}{3}-\frac{4}{x})

Выполним преобразования:

(\frac{x}{3}-\frac{4}{x})^2=\frac{x^2}{9}+\frac{16}{x^2}-\frac{8}{3}=\frac{1}{3}(\frac{x^2}{3}+\frac{48}{x^2})-\frac{8}{3}

Отсюда выразим

\frac{x^2}{3}+\frac{48}{x^2}=3(\frac{x}{3}-\frac{4}{x})^2+8

Получим уравнение, равносильное исходному:

3(\frac{x}{3}-\frac{4}{x})^2+8=10(\frac{x}{3}-\frac{4}{x})

Сделаем замену переменной

t=\frac{x}{3}-\frac{4}{x} \\\ 3t^2-10t+8=0 \\\ t_1=2, t_2=\frac{4}{3}

Вернемся к х:

1) \frac{x}{3}-\frac{4}{x}=2 \\\ x^2-6x-12=0 \\\ x_{1,2}=\frac{6б\sqrt{84}}{2}=3б\sqrt{21}

2) \frac{x}{3}-\frac{4}{x}=\frac{4}{3} \\\ x^2-4x-12=0 \\\ x_3=-2,x_4=6

Ответ: 3б\sqrt{21}; -2; 6.